THE INSTITUTIONAL CLIMATE THROUGH OF GYMNASTIC ACTIVITY - ANDONAYRE-MUNAYCO, Luis (2024)
A study was carried out that seeks to determine the impact of the development of group gymnastic activities by teachers to improve the institutional climate among the teachers of a state educational institution in the city of Lima, therefore, a research was considered based on group work strategies based on gymnastic activities; An investigation was carried out considering a control group and experimental group. Both groups were evaluated on the institutional climate as a pretest; after nine sessions, a posttest was taken fromthe participating teachers; The control and experimental groups were made up of 34 teachers each; The teachers belong to an educational institution in the Lima district of Los Olivos. The results showed that the experimental group had a significant development of the institutional climate; this when comparing the pretest and posttest; while in the control group the institutional climate was maintained; The parameter used to compare for the related groups was T-Student.